The N-link pendulum: Embedding nonlinear dynamics into the multidimensional scaling method - Machado, J. A. Tenreiro (2015)
This paper explores the use of multidimensional scaling for analyzing the dynamics of the N-link planar pendulum. Several integer- and fractional-order pendular systems are studied based on the time response and energy of the links. The dynamics get increasingly complex and chaotic with the number of degrees-of-freedom. The numerical experiments demonstrate the feasibility of the proposed methodology in analyzing the data and motivate its extension for other performance measures and dynamical systems.